(untitled) (Altre Modernità, 2021)
The article examines The White Robes (Belye odeždy), the second novel by Vladimir Dudincev (1918-1998), a tragic figure in Soviet literature. After Not by Bread Alone (1957), he met with enormous success but was forced into silence due to the political scandal that ensued. The White Robes, written in 1966, but published only twenty years later (1987), is set in the midst of lysenkoism, the violent repression against the scientific community that took place between the 1940s and 1950s. Its protagonists are biologists: understanding nature, being in dialogue with the natural world, is their prerogative to obtain results. Scientific reflection is promptly accompanied by a philosophical one. In an intense discussion on the relationship between man and Nature, the protagonists take up different positions and seem to "wear" animal figures with almost totemic value. The possible configurations of human society, professional relationships and individual experiences are related to animal behavior. The character associated with these animals refers both to their behavior in nature and to the symbolism linked to them in the Russian folk tradition. The search for truth by men of science meets the need for camouflage, the key concept of the plot. Mimicry is seen as a necessary deception to maintain biological variety in the natural world as well as to guarantee freedom of thought and scientific research in a country paralyzed by the regime.